2015
DOI: 10.1177/1933719114542022
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management Affects Outcomes in the Pathophysiology of an Endometriosis Model

Abstract: We have previously shown detrimental effects of stress in an animal model of endometriosis. We now investigated whether the ability to control stress can affect disease parameters. Endometriosis was surgically induced in female Sprague-Dawley rats before exposing animals to a controllable (submerged platform) or uncontrollable (no platform) swim stress protocol. Corticosterone levels and fecal pellet numbers were measured as an indicator of stress. Uncontrollable stress increased the number and size of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 38 publications
1
55
0
1
Order By: Relevance
“…Prior studies in our laboratory found that psychological stress can exacerbate endometriosis symptoms in this model (9). Stress is known to be involved in the etiology of a variety of disease states (39, 40), yet few studies have examined how physical activity can ameliorate the effects of stress.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Prior studies in our laboratory found that psychological stress can exacerbate endometriosis symptoms in this model (9). Stress is known to be involved in the etiology of a variety of disease states (39, 40), yet few studies have examined how physical activity can ameliorate the effects of stress.…”
Section: Discussionmentioning
confidence: 69%
“…Animals were handled (5 min/d) for 7 days prior to beginning the experiments in order to reduce manipulation stress, and vaginal cytological smears carried out daily to verify reproductive cycles (9). Experiments were carried out at the same time of day (9 am to 12 pm) to minimize the influence of circadian rhythms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were part of a larger set of rats from our previous publication. 28 Rats were randomly assigned to either sham surgery or surgical induction of endometriosis (endo). All animals were maintained in a bio-bubble facility room on a 12-hour light-dark cycle and at constant temperature (23 C).…”
Section: Animal Modelmentioning
confidence: 99%
“…Endometriosis was surgically induced as previously described elsewhere (29,30). Briefly, rats were anesthetized with isoflurane and four pieces of the right uterine horn were auto transplanted to 4 different blood vessels in the intestinal mesentery.…”
Section: Methodsmentioning
confidence: 99%